From the FDI Triad to multiple FDI poles? - Persephone Economou; Karl P. Sauvant (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Twenty years ago, in the inaugural issue of the World Investment Report, the United Nations highlighted a shift in the global pattern of foreign direct investment (FDI) from bipolar, dominated by the United States and the European Community, to tri-polar (the FDI Triad), dominated by the European Community, the United States and Japan.
Keywords: 330